Edukasi Pengelolaan Sampah Rumah Tangga Menjadi Ecobrick di Desa Cot Seumeureng Aceh Barat - Rahma, Endah Anisa; Najmi, Nurul; Suriani, Mai; Oktavinanda, Giovanni; Gazali, Mohamad; Syafitri, Rina; Hasni, Jusnaini; Rahmatillah, Refanja (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
In Indonesia, plastic waste is the main source of the build up of garbage in landfill sites. It is also kinds of garbage that pollutes the environment because it is difficult to decompose in natural process. The problems occur in the society now is that they are unable to manage their waste effectively. If the problem is not managed properly, it will bring negative effects for the environment. This community services activity was held in Cot Seumeureng Village, West Aceh. The aim of this community service activity is to increase the society awareness on the importance of protecting and taking care of the environment in order to be clean and healthy and free of plastic waste. The methods used in this activity are the ecobrick management training and recycle it to be household appliances. The result of this activity is the increasing awareness of the society in managing the waste and recycle it using ecobrick and also to support the economy of the society in the area. Therefore, it can be concluded that plastic waste can help the community’s income by the use of plastic waste to be ecobricks and protect the environment from plastic waste.